Digitalization of Public Services and Smart Governance: Normative Gaps and Legal Opportunities in Central Aceh - Rahayu Fitri, Rizki; Addy Lestya Wardhani, Lita Tyesta; Wesnaeni, Fifiana (Jurnal Cakrawala Hukum, 2025)
Indonesia's regional autonomy framework places the primary burden of public service delivery on district-level governments, yet the legal architecture governing digital transformation at this level remains structurally deficient. This study examines the juridical dimensions of public service digitalization in Central Aceh Regency, specifically analyzing the normative gaps, institutional barriers, and legal opportunities that shape its trajectory toward smart governance. Employing a normative juridical approach with statute, conceptual, and comparative analytical methods, the study finds that digitalization in Central Aceh is largely symbolic rather than substantive. Presidential Regulation No. 95 of 2018 on SPBE lacks enforcement mechanisms capable of compelling genuine compliance at the district level, while Law No. 25 of 2009 on Public Services contains no affirmative digital service mandate. The absence of a Qanun on Digital Services an instrument legally available under Aceh's special autonomy framework has created a critical normative vacuum that allows institutional fragmentation, low ASN digital literacy, and authority-oriented bureaucratic culture to persist unchallenged. Juridical opportunities exist through Qanun legislation under Article 235(1) of Law No. 11 of 2006, the proactive disclosure obligations of Law No. 14 of 2008 on Public Information Disclosure, and regional autonomy provisions enabling locally adaptive governance models. Genuine bureaucratic repositioning toward smart governance requires enforceable legal instruments, not merely digital infrastructure.